Cooling or Warming the Esophagus to Reduce Esophageal Injury During Left Atrial Ablation in the Treatment of Atrial Fibrillation - Zagrodzky, Jason; Gallagher, Mark M.; Leung, Lisa W.M.; Sharkoski, Tiffany; Santangeli, Pasquale; Tschabrunn, Cory; Guerra, Jose M.; Campos, Bieito; MacGregor, John; Hayat, Jamal; Clark, Brad; Mazur, Alex; et al. (Journal of Visualized Experiments, 2020)
Ablation of the left atrium using either radiofrequency (RF) or cryothermal energy is an effective treatment for atrial fibrillation (AF) and is the most frequent type of cardiac ablation procedure performed. Although generally safe, collateral injury to surrounding structures, particularly the esophagus, remains a concern. Cooling or warming the esophagus to counteract the heat from RF ablation, or the cold from cryoablation, is a method that is used to reduce thermal esophageal injury, and there are increasing data to support this approach. This protocol describes the use of a commercially available esophageal temperature management device to cool or warm the esophagus to reduce esophageal injury during left atrial ablation. The temperature management device is powered by standard water-blanket heat exchangers, and is shaped like a standard orogastric tube placed for gastric suctioning and decompression. Water circulates through the device in a closed-loop circuit, transferring heat across the silicone walls of the device, through the esophageal wall. Placement of the device is analogous to the placement of a typical orogastric tube, and temperature is adjusted via the external heat-exchanger console.
CRIS-Team Scopus Importer:2020-04-10